2014
DOI: 10.2147/idr.s55380
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in the treatment of dengue shock syndrome

Abstract: Dengue infection causes significant morbidity and mortality in over 100 countries worldwide, and its incidence is on the rise. The pathophysiological basis for the development of severe dengue, characterized by plasma leakage and the “shock syndrome” are poorly understood. No specific treatment or vaccine is available, and careful monitoring and judicious administration of fluids forms the mainstay of management at present. It is postulated that vascular endothelial dysfunction, induced by cytokine and chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
(49 reference statements)
0
21
1
1
Order By: Relevance
“…6 Shashidhara et al, (2013) conducted an experiment to evaluate the Effect of High Dose of Steroid on Platelet count in Acute Stage of Dengue Fever with Thrombocytopenia and concluded that at a high dose dexamethasone regimen was not effective in achieving a higher rise in the platelet count in the acute stage of dengue fever. 23 The study of Rajapakse et al, (2014) showed that there is currently no high quality evidence supporting the beneficial effects of corticosteroids for treatment of shock, prevention of serious complications or increasing platelet counts. 24 Panpanich et al, (2006) observed an increased mortality after the use of steroids in DSS and DHF and gave opinion that it was difficult to conduct a study on life threatening illnesses like DSS and DHF, as steroids would have compounding effects on the outcome of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Shashidhara et al, (2013) conducted an experiment to evaluate the Effect of High Dose of Steroid on Platelet count in Acute Stage of Dengue Fever with Thrombocytopenia and concluded that at a high dose dexamethasone regimen was not effective in achieving a higher rise in the platelet count in the acute stage of dengue fever. 23 The study of Rajapakse et al, (2014) showed that there is currently no high quality evidence supporting the beneficial effects of corticosteroids for treatment of shock, prevention of serious complications or increasing platelet counts. 24 Panpanich et al, (2006) observed an increased mortality after the use of steroids in DSS and DHF and gave opinion that it was difficult to conduct a study on life threatening illnesses like DSS and DHF, as steroids would have compounding effects on the outcome of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…23 The study of Rajapakse et al, (2014) showed that there is currently no high quality evidence supporting the beneficial effects of corticosteroids for treatment of shock, prevention of serious complications or increasing platelet counts. 24 Panpanich et al, (2006) observed an increased mortality after the use of steroids in DSS and DHF and gave opinion that it was difficult to conduct a study on life threatening illnesses like DSS and DHF, as steroids would have compounding effects on the outcome of the disease. 7 In view of these observations, the empirical use of steroids may be avoided in dengue fever with thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Conversely majority of the clinical studies have failed to demonstrate this benefit. 15 Future studies segregating the patients with thrombocytopenia with different mechanisms and targeting the treatment may provide the answers to the dogma of steroid usage in dengue infection.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid-mediated stimulation of the hypothalamic-pituitaryadrenal axis can also drive lymphocytopenia [24], or it may promote exaggerated pro-inflammatory responses that eventually cause a worsening of the pathogenic condition [126]. Due to concerns regarding these side-effects, the World Health Organization does not at present recommend glucocorticoids for treatment [131,132]. Furthermore, it is now known that the effectiveness of corticosteroid treatment greatly depends on the timing of drug administration.…”
Section: Corticosteroid Based Therapeutic Approaches and Their Limitamentioning
confidence: 99%